Mencari Titik : Temu Rekonsiliasi Teoretis Antara Konsep Islam, Liberalisme, Dan Sosialisme Dalam Politik Di Indonesia Abad Ke-21: Finding the Common Ground: A Theoretical Reconciliation Between Islamic, Liberal, and Socialist Concepts in 21st-Century Indonesian Politics - MUALIPATUS S, SITI (Faculty of Social and Political Sciences - Universitas Wahid Hasyim, 2025)
This study aims to analyze and identify the common ground among the concepts of Islam, Liberalism, and Socialism within the political context of 21st-century Indonesia. Using a descriptive qualitative analitic approach, the research examines how Islamic values such as shura (consultation), ‘adl (justice), hurriyyah (freedom), and musawah (equality), along with liberal values such as individual freedom, democracy, and the free market, as well as socialist values including equality, cooperation, and social compassion, shape political policies within the state. The findings indicate that various aspects and policies of governance can be effectively developed through a synthesis of the best elements from these three ideological frameworks. The study concludes that the integration of selected values from Islam, Liberalism, and Socialism plays a significant role in building a conducive political system, protecting citizens’ rights, and fostering global cooperation. Nevertheless, this integration also faces numerous challenges and opens further discussions on the evolution of political thought in 21st-century Indonesia. Keywords: Islam, Liberalism, Socialism, Political Policy